2014
DOI: 10.1007/jhep10(2014)169
|View full text |Cite
|
Sign up to set email alerts
|

OPE of the energy-momentum tensor correlator and the gluon condensate operator in massless QCD to three-loop order

Abstract: The correlator of two gluonic operators plays an important role for example in transport properties of a Quark Gluon Plasma (QGP) or in sum rules for glueballs.In [1] an operator product expansion (OPE) at zero temperature was performed for the correlators of two scalar operators O 1 = − 1 4 G µν G µν and two QCD energy-momentum tensors T µν . There we presented analytical two-loop results for the Wilson coefficient C 1 in front of the gluon condensate operator O 1 . In this paper these results are extended to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 50 publications
(85 reference statements)
2
36
0
Order By: Relevance
“…We have also observed that the O(g 4 ) log-divergent contact term in C (S) 1 [11][12][13] mixes in Eq. (3.10) with the scheme-dependent divergences to the order of g 4 due to the second coefficient of the anomalous dimension of F 2 (Sec.…”
Section: Low-energy Theorem and Perturbation Theorysupporting
confidence: 51%
See 3 more Smart Citations
“…We have also observed that the O(g 4 ) log-divergent contact term in C (S) 1 [11][12][13] mixes in Eq. (3.10) with the scheme-dependent divergences to the order of g 4 due to the second coefficient of the anomalous dimension of F 2 (Sec.…”
Section: Low-energy Theorem and Perturbation Theorysupporting
confidence: 51%
“…A previous perturbative lower-order computation appeared in [14]. We pass from the perturbative OPE in the momentum representation [11][12][13] in Apps. B.1 and B.4 to the OPE in the coordinate representation by the Fourier transform in Apps.…”
Section: Plan Of the Papermentioning
confidence: 99%
See 2 more Smart Citations
“…This challenge has indeed been addressed first on the level of the Operator Product Expansion (OPE) in [23], and later by considering the full NLO spectral function in [24] (see also the related T = 0 work of [25,26]). While consistent with known sum rules [27,28] as well as the arguments of [29] concerning the UV behavior of various Green's functions, the latter of these calculations delivered somewhat surprising results.…”
Section: Jhep03(2015)138mentioning
confidence: 99%